2020
DOI: 10.3390/ma13051167
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of A 1940 nm Thulium-Doped Fiber Laser and A 1470 nm Diode Laser for Cutting Efficacy and Hemostasis in A Pig Model of Spleen Surgery

Abstract: Partial and total splenectomies are associated with a high risk of substantial blood loss. Lasers operating at wavelengths strongly absorbed by water have the potential to improve hemostasis and cut while providing a narrow zone of thermal damage. The aim of this study is to compare a thulium-doped fiber laser (TDFL) emitting a wavelength of 1940 nm and a diode laser (DL) operating at 1470 nm for spleen surgery in a pig model. A partial splenectomy and spleen incisions were made in 12 animals using the two las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
(28 reference statements)
1
13
0
Order By: Relevance
“…Considering that the bleeding with both lasers was comparable and that the TDFL tended to ensure better hemostasis, it can be assumed that the deeper tissue damage by the diode laser is unfavorable. In our previous reports, we have shown that the thulium-doped fiber laser can efficiently cut parenchymal organs in pigs (i.e., liver and spleen), while producing minimal zones of thermal damage sufficient for hemostasis (maximum depth: 1157.5 µm on day 7 for spleen and 1818.7 µm on day 7 for liver) [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that the bleeding with both lasers was comparable and that the TDFL tended to ensure better hemostasis, it can be assumed that the deeper tissue damage by the diode laser is unfavorable. In our previous reports, we have shown that the thulium-doped fiber laser can efficiently cut parenchymal organs in pigs (i.e., liver and spleen), while producing minimal zones of thermal damage sufficient for hemostasis (maximum depth: 1157.5 µm on day 7 for spleen and 1818.7 µm on day 7 for liver) [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The beam quality for the output radiation was of high quality, allowing for its use in thin treatment probes (less than 50 µm in diameter). The design and detailed physical parameters of the laser have been described in detail elsewhere [8,26,27].…”
Section: Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of TDFL in solid organ parenchyma surgery is still uncommon. Boguslawa et al, showed the zones of thermal tissues achieved by TDFL were narrower compared to Diode Laser and Nd:YAG laser, therefore TDFL laser seems to be an effective tool for precise surgical procedures with narrow and controlled zone of destruction of the adjacent tissue [ 11 ]. Maciej et al, showed the efficacy of TDFL in cutting with a narrow zone of thermal injury and provides good hemostasis during partial liver resection and liver tissue incision.…”
Section: Introductionmentioning
confidence: 99%
“…The authors would like to add the following sentence to the “Funding” section of their article [ 1 ]:…”
mentioning
confidence: 99%